The Implementation of Passive Removal Granting for Corruption Criminal Acts - Kholis, Ahmad Nur; Suharto, Rakhmat Bowo (Law Development Journal, 2021)
Conditional release is one of the rights of every convict who is serving a prison sentence in a Correctional Institution, including convicts of criminal acts of corruption. Since the issuance of Government Regulation Number 99 of 2012, the conditions that must be met in granting parole for convicts of criminal acts of corruption have been tightened on the basis of a sense of community justice. This study aims to examine and analyze the implementation of the provision of parole for convicts of criminal acts of corruption at the Class I Penitentiary in Semarang, as well as the obstacles faced in its implementation. This study uses an empirical juridical approach with analytical descriptive research methods. The data used are primary and secondary data obtained by interview, observation and literature methods. The results of the study concluded that the implementation of the provision of parole for convicts of criminal acts of corruption at the Class I Penitentiary in Semarang was carried out in accordance with the rules of Government Regulation No. 99 of 2012. In practice, not all convicts of criminal acts of corruption can obtain parole because the conditions are not met. Obstacles experienced in the implementation of the provision of parole for convicts of criminal acts of corruption include: convicts are unable to pay fines and/or replacement money, the implementation of social work assimilation must involve third parties as a condition for proposing parole and the existence of information as a justice collaborator from enforcement officers in another law. To overcome these obstacles, it can be done by coordinating and proposing leave before being released.